Perceptions of Grammar Translation Method: Insights from Vocational Students in Audio-visual Engineering - Maulida Salsabila (Universitas Negeri Surabaya, 2026)
The Grammar Translation Method (GTM) has long been utilized in English language teaching, particularly in contexts where accuracy and grammatical mastery are emphasized. However, its relevance in vocational education, especially in technical fields such as Audio-Visual Engineering, remains a subject of debate. This study aims to explore vocational students’ perceptions of the Grammar Translation Method in learning English grammar and to examine its perceived strengths and limitations in supporting their learning needs. Employing a qualitative descriptive approach, the research involved students from a vocational high school majoring in Audio-Visual Engineering. Data were collected through questionnaires and semi-structured interviews to capture students’ experiences, attitudes, and reflections toward the use of GTM in the classroom. The findings indicate that students perceive GTM to be helpful in improving their understanding of grammatical rules, vocabulary accuracy, and sentence structure, particularly when dealing with technical texts related to their field. The use of the first language (L1) is considered beneficial in clarifying complex concepts and reducing learning anxiety. However, students also highlight limitations of GTM, such as limited opportunities for speaking practice and insufficient development of communicative competence. Despite these drawbacks, GTM is viewed as relevant when applied selectively and combined with more communicative approaches. This study concludes that while GTM alone may not fully address the communicative demands of vocational students, it can serve as an effective foundational method for grammar comprehension when adapted to vocational contexts. The findings provide pedagogical implications for English teachers in vocational schools to implement GTM in a balanced and context-sensitive manner.